A subpopulation of human B lymphocytes can express a functional Tissue Factor in response to phorbol myristate acetate - Mechiche, Houria; Cornillet-Lefebvre, Pascale; Nguyen, Philippe (Thrombosis and Haemostasis, 2005)
Tissue Factor (TF, CD142) is a transmembrane glycoprotein that belongs to the cytokine receptor superfamily. This multifunctional protein is constitutively present in most tissues. Among circulating blood cells, TF expression is known to be restricted to monocytes which do not constitutively produce TF but express TF in response to various stimuli. Here, we report that highly purified B lymphocytes can support a procoagulant activity (PCA) in response to phorbol myristate acetate (PMA).Using flow cytometry (FCM), we observed that a subpopulation of B lymphocytes (CD19+) can expressTF and anionic phospholipids in response to PMA. TF protein was identified and characterized by immunofluorescence, immunocytochemistry and electronic microscopy. Using RT-PCR, we identified the presence of TF mRNA in response to PMA. In conclusion, B lymphocytes are a potential source of functional TF in human.
Keywords: Tissue factor; procoagulant activity; B lymphocyte; PMA